Autor[izar-se]: subjetivação e literatura pela obra de Maura Lopes Cançado - Graglia, Juliana Guida Vieira (2020)
The encounter with the writing of Maura Lopes Cançado is largely marked by a hyperpersonification of the author, which produces a depotentializing noise from the literary experience. Generated by the self-referential marks present in the texts, as well as by the specificity or eccentricity of the identity roles attributed to them in life: that of vain and immoral woman, that of madwoman, that of criminal, etc. Filters that stand in the way of reading and threaten to turn texts into mere revelation indices, appendix to the author character. A condition present in the act of reading, and also in the act of writing, in which the eagerness to report itself constitutes the self, as a responsive, recognizable and socially accepted subject. The concept of authorship thus overflows from the specific territory of aesthetics to the ethical regime of interpellation, reveals itself as a mode of subjectivation. But what are the criteria, which truth regime dictates the norms for being considered a subject? The metaphysical heritage, establishing truth as a presence, privileges being over becoming and excludes plurality as a signifier, everything that does not permanently crystallize. In this order of discourse, the univocity of voices, difference, has to be overcome by identity and semantic logic. Grounded in this ground of selfreferentiality, contemporary literature can create a field of tension between the poles of dominant capitalist narcissism and the criticism of the subject of truth. After all, when it inserts it in fiction, it discredits, as it were, this coherent, monolithic subject. Opening possible outlets for the desert of consciousness. The fabulous skill - as invisible as inherent in language - it works intensively, affectionately, by explaining the space between the shackles of discourses, of orders of ways of life. Fiction can be a potent tool in this authoring exercise. Escaping both the narcissistic, hyperpersonal statement and the aphonia of the a-personal, opening impersonal ground for difference to take a place